2009
DOI: 10.1097/bpb.0b013e32832e4737
|View full text |Cite
|
Sign up to set email alerts
|

A rare variant of tibial hemimelia and its treatment

Abstract: Tibial hemimelia is a rare condition. We present a variant of tibial hemimelia not reported in literature before. In this variant, we were able to successfully salvage the limb with excellent function to carry on with life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Our case neither conforms to any of the 4 types of Jones’ classification, nor the Weber- classification or Paley- classification. Shrivastava [10] present a variant of tibial hemimelia in 2009, which was very similar to our case. That case was a 9-year-old Asian boy who was diagnosed with tibial hemimelia when he was 1 week old, because of the absence of tibia shaft, fibular become hypertrophied, shortened and curved after loading the body weight.…”
Section: Discussionsupporting
confidence: 88%
“…Our case neither conforms to any of the 4 types of Jones’ classification, nor the Weber- classification or Paley- classification. Shrivastava [10] present a variant of tibial hemimelia in 2009, which was very similar to our case. That case was a 9-year-old Asian boy who was diagnosed with tibial hemimelia when he was 1 week old, because of the absence of tibia shaft, fibular become hypertrophied, shortened and curved after loading the body weight.…”
Section: Discussionsupporting
confidence: 88%
“…One example is the case report by Shrivastava et al of an intercalary deficiency where the central portion of the tibia is missing but the proximal and distal tibia is intact [50]. …”
Section: Classificationmentioning
confidence: 99%
“…It has been suggested that treatment should start as early as possible in order to achieve early and maximum alignment between the knee and the ankle 5,17,30 . Various reconstructive methods have been described to avoid amputation 1,12,19,24,27,30 . Brown, in 1965, described the cases of 3 patients who were managed with fibular centralization combined with arthrodesis of the knee and Syme amputation 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Tibial hemimelia is a rare congenital anomaly that may be associated with other congenital anomalies, deficiencies, and duplications 1-12 . The spectrum of pathological findings is much wider, and nearly 60% of patients with tibial hemimelia have other associated congenital anomalies such as lobster claw deformity, hand syndactyly, polydactyly, and/or foot ray duplication 6-8,13,14 .…”
mentioning
confidence: 99%